Thermal Properties Enhancement of Vertically Aligned Carbon Nanotubes-Based Metal Nanocomposites as Thermal Interface Materials - Zhang, Qiuhong; A. Calderon, Brian; R. Ebbing, Charles; J. Elston, Levi; W. Byrd, Larry; Tsao, Bang-Hung (Frontiers in Materials, 2020)
Increasing power densities in high-power electronic packages require advanced heat dissipation from their respective thermal interface materials (TIMs). Modern TIMs does not accommodate both factors of thermal performance and mechanical compliance with increasing device power density. Vertically aligned carbon nanotubes (VACNT) are advantageous in that their intrinsic properties promote both high thermal conductivity while maintaining a mechanically flexible/compliant interface. Therefore, it is a promises approach to use of carbon nanotubes (CNTs), specialty VACNTs, to make a novel interface heat transfer material. However, the high thermal contact resistance between VACNTs and substrate(s) has been a big issue to limit its application. In this study, the effect of post-processing techniques such as plasma treatment and surface metallization of VACNT layer (directly grown on Cu substrate) on interfacial properties of CNTs with mating substrate were explored and the thermal properties were evaluated via Laser Flash testing system. Thermal test results demonstrated that modifying the surface of the VACNT layer is effective method to improve interfacial attachment between CNTs and mating substrate. Results indicated that, among different VACNT surface modification methods, the plasma treated VACNT layer surface promote the best thermal properties of VACNT-based metal nanocomposite (MNC) as TIM. Compared to the unmodified VACNT layer, in this study, the interphase thermal resistance of the Cu/VACNT/matched substrate sample made from the plasma treated VACNT layer was reduced approximately 80%.